Phytophagous consumption by frogs inhabiting bromeliads from Atlantic Forest. Issue 2 (4th March 2022) - Sabagh, Leandro T.; Neutzling, Alexandre S.; Rocha, Carlos F.D.
Abstract : Analyses of the diets of frog species in a range of different habitats have shown that these amphibians feed primarily on arthropods. In general, frogs are not selective predators, but may vary in their capture mode along a continuum between active and passive foraging. In the present study, we assessed the diet of two bromeliad-breeding frogs of the genus Ololygon (= Scinax ) through taxonomic and functional identification (trophic guilds). We innovate in use of trophic guilds of frogs' preys and use the phytophagous consumption as proxy for favoring bromeliads by frogs. We also assessed the potential relationship between the size of the frogs and that of the prey they ingest, whether consumption rates varied seasonally, and the foraging mode. The results indicated a diet composed predominantly of phytophagous arthropods for both Ololygon species ( O. littorea and O. perpusilla ). Most of the arthropods consumed belonged to the orders Hemiptera, Diptera and Hymenoptera. We found no significant differences among the number of arthropods ingested in the rainy and in the dry seasons in either Ololygon species, nor significant relationship found between the frog size and corresponding prey ingested by individual frogs. The foraging mode of frogs was restricted only to vegetative parts of bromeliads and they did not feed on any potential pollinators. Taken together, these results suggested that frogs may favor the host bromeliad and suggest a potential trophic cascade among frogs, bromeliads, and phytophagous arthropods.